Knowledge and Healthy Life Behavior in Facing the New Normal for YARSI University Faculty of Medicine Students Class of 2018 and 2020 - Nida Azamia; Kenconoviyati (Nusantara Science and Technology Proceedings, 2022)
Health is an important component in addition to the economy and educa-tion in Indonesia because through health, individuals can have wider op-portunities and abilities to fulfill their educational and economic needs as a process of improving the quality of resources. Day by day the incidence of COVID-19 is increasing. Making peace with the corona virus makes life return to the new normal. This research was carried out because there was no research related to the relationship between knowledge and healthy living behavior in the face of the new normal for students of the Faculty of Medicine, YARSI University Class of 2018 and 2020. This research activity has an analytic nature with a cross sectional approach. Collected with stratified random sampling, and the determination of the sample size using Consecutive sampling. The sample in this research activity was active students of the Faculty of Medicine, YARSI University batch 2018 and 2020 as many as 220 students, consisting of 112 students of 2018 and 108 students of 2020. The inclusion criteria were students who were active and willing to be respondents. Bivariate data analysis using Fisher's test. The results show that the p-value is 0.000 < 0.005 which can be interpreted as "There is a significant relationship between knowledge of healthy living behavior and healthy living behavior in the new normal era for students of the Faculty of Medicine, YARSI University Class of 2018 and 2020". Behavior that is based on knowledge will last longer than behavior that is not based on knowledge.